A systematic review and meta-analysis of Comaneci/Cascade temporary neck bridging devices for the treatment of intracranial aneurysms - Sun, Bowen; Lan, Shuai; Sawant, Harshal; Li, Yuchen; Ling, Yeping; Zhang, Bohan; Wu, Pei; Wang, Chunlei; Shi, Huaizhang; Xu, Shancai (Frontiers in Human Neuroscience, 2023)
Background The temporary neck bridging devices represented by Comaneci and Cascade are a type of promising endovascular device for the treatment of intracranial bifurcation or wide-necked aneurysms. This systematic review and meta-analysis aim to assess the efficacy and safety of Comaneci/Cascade devices for the treatment of intracranial aneurysms. Methods We performed a systematic literature search on articles in PubMed, Embase, and Web of Science that evaluated the efficacy and safety of Comaneci/Cascade devices for endovascular treatment of intracranial aneurysms, based on the Preferred Reporting Items for Systematic Reviews and Meta Analytics (PRISMA) guideline. We extracted the characteristics and treatment related information of patients included in the study, recorded the rate of technical success, procedural related complications, and angiographic outcomes. The angiographic outcome was evaluated based on Raymond Roy classification, and adequate occlusion was defined as Raymond Ray I + II. Results Nine studies comprising 253 patients with 255 aneurysms were included. Among them, eight studies were conducted in Europe, one study was conducted in the USA. All these studies were retrospective. 206 aneurysms (80.78%) were ruptured. The vast majority of patients with ruptured aneurysms did not receive antiplatelet therapy. The rate of technical success was 97.1% (95% CI, 94.9 to 99.3%, I2 = 0%). The rate of periprocedural clinical complications was 10.9% (95% CI, 5.4 to 22.1%, I2 = 54%). The rate of complete occlusion (RR1) and adequate occlusion (RR1 + RR2) on immediate angiography after the procedure were 77.7% (95% CI, 72.7 to 83.2%, I2 = 35%) and 98% (95% CI, 95.9 to 100%, I2 = 0%) respectively. The rate of complete occlusion (RR1) and adequate occlusion (RR1 + RR2) on the last follow-up angiography were 81.2% (95% CI, 69.2 to 95.2%, I2 = 81%) and 93.7% (95% CI, 85.6 to 100%, I2 = 69%) respectively, with follow-up range from 3 to 18 months. 22/187 (11.76%) cases of aneurysms progressed during the follow-up period. 39/187 (20.86%) cases of aneurysms received additional treatment during the follow-up period. No fatal complications occurred during the treatment. Conclusion The Comaneci/Cascade device can be used as an auxiliary treatment for intracranial aneurysms, with a good occlusion effect, but the incidence of complications still needs to be monitored.